Investigating under-reported human papillomavirus genotypes in Grenadian women through self-sampling for cervical cancer screening - Frances McGill; Paul J. Fields; Aví Bahadoor-Yetman; Erin Salter Manglardi; Ronelle Bailey; Kritika Padala; Jessica Lendore; Tiffany John-Ballantyne; Sasha Lake (Pan American Health Organization, 2024)
Objective. To compare the adequacy, agreement, and acceptability of Papanicolaou testing (cytology) for cervical cancer screening using self-collected samples compared to physician-collected samples in Grenada in the Caribbean. Furthermore, the study identifies the human papillomavirus (HPV) genotypes present among asymptomatic women testing positive for HPV, the etiologic cause of cervical cancer. Methods. Participants were divided into two groups and two cervical samples were collected from the women in each group: a self-collected sample and a physician-collected sample. Cervical specimens were tested for cytology and HPV. HPV genotyping was performed on positive specimens. Results. Self-collected samples were adequate and in agreement with physician-collected samples, showing no difference between the two sampling methods. Oncogenic high-risk HPV genotypes were identified in cervical samples which were positive for atypical squamous cells and low-grade squamous intraepithelial lesions. The high-risk HPV genotypes found, notably HPV 45 and 53, differed from those most commonly reported. Although the commonly reported high-risk genotypes HPV 16 and 18 were found, so were 31, 33, 35, 52, 66, 68, and 82. Conclusions. Using self-collection facilitated the discovery of unexpected HPV genotypes among asymptomatic women in Grenada. These findings add new information to the literature regarding cervical cancer and neoplasia screening and HPV genotypes in the Caribbean. This genotype information may impact surveillance of women with low-grade lesions, HPV vaccine selection, and possibly further vaccine research. Research regarding HPV in Caribbean pathology samples of cervical neoplasia and cancer is needed.